The youth tourist satisfaction of domestic tourism product and electronic word-of-mouth promotion / Samsiariah Aliyas - Aliyas, Samsiariah (2013)
The focus of this study was to gain a better understanding of the requirements of youth user in Malaysia, the levels of satisfaction associated with the domestic tourism product, the dissemination behaviour by using electronic word-of-mouth (e-WOM) and the mediating effect of satisfaction on the tourism product and e-WOM. Quantitative study method was undertaken to examine the level of satisfaction for domestic tourism products among youth traveller in the country and the e-WOM promotion. A purposive sample of youth tourist, age between 15 to 30 who has experience of using the domestic tourism product was selected. Data that was collected via self-completed questionnaire was tested and analysed by using the descriptive and inferential statistics. The result indicates that in association with the dimensions of tourism product, comprising; accommodation facility, transportation and attraction area, the youth tourist are satisfied with the domestic tourism product available for their usage. In addition, mediating effects of satisfaction is partially mediate the relationship between tourism product and e-WOM. The findings should provide valuable information and insights on the current trend of youth tourism in the country and thus strengthening the current literatures available for this area of study. Practical implications are drawn for the development and marketing of domestic tourism products for the youth market.